Selective Dynamical Imaging of Interferometric Data - Farah Joseph; Galison Peter; Akiyama Kazunori; Bouman Katherine L.; Bower Geoffrey C.; Chael Andrew; Fuentes Antonio; Gómez José L.; Honma Mareki; Johnson Michael D.; Kofuji Yutaro; Marrone Daniel P.; et al. (IOP Publishing Ltd, 2025)
Recent developments in very long baseline interferometry (VLBI) have made it possible for the Event Horizon Telescope (EHT) to resolve the innermost accretion flows of the largest supermassive black holes on the sky. The sparse nature of the EHT's (u, v)-coverage presents a challenge when attempting to resolve highly time-variable sources. We demonstrate that the changing (u, v)-coverage of the EHT can contain regions of time over the course of a single observation that facilitate dynamical imaging. These optimal time regions typically have projected baseline distributions that are approximately angularly isotropic and radially homogeneous. We derive a metric of coverage quality based on baseline isotropy and density that is capable of ranking array configurations by their ability to produce accurate dynamical reconstructions. We compare this metric to existing metrics in the literature and investigate their utility by performing dynamical reconstructions on synthetic data from simulated EHT observations of sources with simple orbital variability. We then use these results to make recommendations for imaging the 2017 EHT Sgr A* data set.